New nomenclatural combinations and a new name in Pseudolysimachion (Plantaginaceae s. l. = Veronicaceae s. str.) and Phlomoides (Lamiaceae): taxa occurring in Ukraine - Ostapko, V.M. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
Seven new nomenclatural combinations and one new name in
Pseudolysimachion (Plantaginaceae s.l = Veronicaceae s. str.)
and Phlomoides (Lamiaceae) are proposed for taxa occurring in
Ukraine: Pseudolysimachion cretaceum (Ostapko) Ostapko, comb.
nov. (Veronica cretacea Ostapko), P. donetzicum (Ostapko) Ostapko, comb. nov. (V. donetzica Ostapko), P. grynianum (Klokov)
Ostapko, comb. nov. (V. gryniana Klokov), P. paczoskianum
(Klokov) Ostapko, comb. nov. (V. paczoskiana Klokov), P. tzvelevii Ostapko, nom. nov. (V. pontica Ostapko, 1994, nom. illeg.,
non Wettst., 1890, nec Velen., 1894), P. semiglabratum (Ostapko)
Ostapko, comb. nov. (V. semiglabrata Ostapko), P. borysthenicum
(Ostapko) Ostapko, comb. nov. (V. borysthenica Ostapko), and
Phlomoides stepposa (Klokov) Ostapko, comb. nov. (Phlomis stepposa Klokov). Для таксонів, поширених в Україні, запропоновано сім нових номенклатурних комбінацій і одна нова назва у родах Pseudolysimachion (Plantaginaceae s. l = Veronicaceae s. str.) та Phlomoides (Lamiaceae): Pseudolysimachion cretaceum (Ostapko) Ostapko, comb. nov. (Veronica cretacea Ostapko), P. donetzicum (Ostapko) Ostapko, comb. nov. (V. donetzica Ostapko), P. grynianum (Klokov) Ostapko, comb. nov. (V. gryniana Klokov), P. paczoskianum (Klokov) Ostapko, comb. nov. (V. paczoskiana Klokov), P. tzvelevii Ostapko, nom. nov. (V. pontica Ostapko, 1994, nom. illeg., non Wettst., 1890, nec Velen., 1894), P. semiglabratum (Ostapko) Ostapko, comb. nov. (V. semiglabrata Ostapko), P. borysthenicum (Ostapko) Ostapko, comb. nov. (V. borysthenica Ostapko), and Phlomoides stepposa (Klokov) Ostapko, comb. nov. (Phlomis stepposa Klokov). Для таксонов, встречающихся в Украине, предложено семь новых номенклатурных комбинаций и одно новое название в родах Pseudolysimachion (Plantaginaceae s. l. = Veronicaceae s. str.) и Phlomoides (Lamiaceae): Pseudolysimachion cretaceum (Ostapko) Ostapko, comb. nov. (Veronica cretacea Ostapko), P. donetzicum (Ostapko) Ostapko, comb. nov. (V. donetzica Ostapko), P. grynianum (Klokov) Ostapko, comb. nov. (V. gryniana Klokov), P. paczoskianum (Klokov) Ostapko, comb. nov. (V. paczoskiana Klokov), P. tzvelevii Ostapko, nom. nov. (V. pontica Ostapko, 1994, nom. illeg., non Wettst., 1890, nec Velen., 1894), P. semiglabratum (Ostapko) Ostapko, comb. nov. (V. semiglabrata Ostapko), P. borysthenicum (Ostapko) Ostapko, comb. nov. (V. borysthenica Ostapko), and Phlomoides stepposa (Klokov) Ostapko, comb. nov. (Phlomis stepposa Klokov).